PENINGKATAN KAPASITAS KELUARGA DENGAN BALITA STUNTING MELALUI EDUKASI, PENDAMPINGAN DAN PELATIHAN DI DESA TAMAN FAJAR KECAMATAN PURBOLINGGO KABUPATEN LAMPUNG TIMUR - Dinutanayo, Wimba Widagdho; Prasetyowati; Sumiyati (Poltekkes Kemenkes Bandung, 2024)
Stunting is one of the main nutritional problems toddlers face worldwide, including in Indonesia. Indonesia's stunting rate has decreased from 26.9% in 2020 to 21.1% in 2022, although it is still far from the national target of 14% by 2024. This community service program aims to increase the capacity of families with stunted toddlers through education, assistance, and training programs in Taman Fajar Village, Purbolinggo District, East Lampung Regency. The methods used include socialization, stunting, and parenting education, provision of supplementary food (PMT), appetite massage training (Tuina massage), hemoglobin level examination and iron tablet supplementation, and parenting assistance for stunted toddlers. The results of the activities showed an increase in family knowledge about stunting and parenting, an improvement in mothers' skills in performing appetite massage techniques, and the delivery of PMT and vitamins for stunted toddlers. The evaluation also showed positive behavioral changes in families in caring for stunted toddlers. Thus, this program effectively intervenes and prevents stunting in the research area.